Analisa Hasil Prediksi Metode Least Square menggunakan Korelasi dan MAPE pada Toko PS - Swanjaya, Daniel; Putra Pamungkas, Danar (Universitas Nusantara PGRI Kediri, 2021)
The sale of cat feed in Toko PS is the main concern of Shop Owners because of the very high enthusiasm of cat owners to buy Cat Feed. However, due to business competition, the sale of Cat Feed is not decisive, so the owner has difficulty in procuring goods. This research predicts the selling of food products in Toko PS using the Least Square method. The results were analyzed using the standby method and MAPE to see the prediction alert level. The obtained values ​​obtained were low, namely between 0 - 0.2 and the MAPE values ​​of 41.8% and 56.3% were categorized as fair and inaccurate. So that the Least Square method is not suitable for predicting to predict fluctuating reference data and with a short period, namely the date or day in the case of Toko PS.